Cardiovagal tone: A predictor of heart rate adjusted augmentation index in men but not in women - Latchman, Peter L.; Thiel, Robert; Gates, Gregory; Zhu, Weili; Axtell, Robert; Gardner, Kenneth; Lunn, William; DeMeersman, Ronald (Open Journal of Molecular and Integrative Physiology, 2017)
2 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
26 citations (Crossref) [2023-10-31] Place: United States Wanigatunga, Amal A. 1Department of Epidemiology, Johns Hopkins University, Baltimore, MD; 2Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA; 3Exercise Science Department, Southern Connecticut State University, New Haven, CT; 4Department of Epidemiology, University of Pittsburgh, Pittsburgh, PA; 5Department of Health Research and Policy and Department of Medicine, Stanford University, School of Medicine, Stanford, CA; 6Feinberg School of Medicine, Northwestern University, Evanston, IL; 7Nutrition, Exercise Physiology and Sarcopenia Laboratory, Jean Mayer United States Department of Agriculture Human Nutrition Research Center on Aging, Tufts University, Boston, MA; 8Department of Biostatistics, University of Florida, Gainesville, FL; and 9Department of Aging and Geriatric Research, University of Florida, Gainesville, FL.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged; 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
89 citations (Crossref) [2023-10-31] Place: United States Fielding, Roger A. Nutrition, Exercise Physiology, and Sarcopenia Laboratory, Jean Mayer USDA Human Nutrition Research Center on Aging at Tufts University, Boston, MA, United States of America. Guralnik, Jack M. Department of Epidemiology and Public Health, University of Maryland School of Medicine, 4655 W. Baltimore Street, Baltimore, MD, United States of America. King, Abby C. Department of Health Research & Policy, and Stanford Prevention Research Center, Department of Medicine, Stanford University Medical School, Stanford, CA, United States of America. Pahor, Marco. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. McDermott, Mary M. Department of Medicine, Northwestern University Feinberg School of Medicine, 750 N Lake Shore Drive, 10th Floor, Chicago, IL, United States of America. Tudor-Locke, Catrine. Department of Kinesiology, University of Massachusetts Amherst, Amherst, MA, United States of America. Tudor-Locke, Catrine. Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, LA, United States of America. Manini, Todd M. Department of Aging and Geriatric Research, University of Florida College of Medicine, Gainesville, FL, United States of America. Glynn, Nancy W. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America. Marsh, Anthony P. Department of Health and Exercise Science, Wake Forest University, Winston-Salem, NC, United States of America. Axtell, Robert S. Department of Exercise Science, Southern Connecticut State University, New Haven, CT. Hsu, Fang-Chi. Department of Biostatistical Sciences, Division of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, United States of America. Rejeski, W Jack. Center for Aging and Population Health, Department of Epidemiology, Graduate School of Public Health, University of Pittsburgh, Pittsburgh, PA, United States of America.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged; 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity; capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
25 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000417650000023, lens.org/040-976-851-672-995 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Aged; Aged; 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty